A REVIEW ON SECONDARY METABOLITES, ANTIOXIDANT AGENT AND ANTIBACTERIAL ACTIVITY OF SALVADORA OLEOIDES L. (International Association of Biologicals and Computational Digest, 2023)
Plants provide all the basic necessary things which are used in routine life. Many drugs are extracted from plants which are helpful in curing many diseases such as diabetes, cancer, inflammation, headache, fever, skin disease, etc. The present review reveals that many secondary metabolites are present in huge amounts and play an important role as antioxidant agents and show antibacterial activity against many bacterial strains. It will be helpful for the extrication of biologically active compounds from the Salvadora genus.
Keywords: Phytochemicals, Anti-oxidant activity and Anti-bacterial activity